Jane Eyre - Francis, Pauline (Evans Brothers Limited, 2005)
In early nineteenth-century England, an orphaned young woman accepts employment as a governess and soon finds herself in love with her employer who has a terrible secret.
Keywords: Juvenile literature-Governesses (England)-Social life and customs (England)-19th century-Children's stories-Fiction